دور تجريف العنق الانتخابي في تدبير العنق سلبيّ العقد سريرياً - العساف, أريج (Latakia University Journal -Medical Sciences Series, 2017)
الهدف من البحث: تقييم فعالية تجريف العنق الانتخابي في تدبير العنق سلبي العقد سريرياً.الطرق: نتائج 75 عملية تجريف عنق أجريت على 52 مريضاً.النتائج: المواقع البدئية كانت: جوف الفم 20، البلعوم الفموي 7، البلعوم الحنجري 4، الحنجرة 21.14 عنق خضع لتجريف عنق أظهر عقداً إيجابية في الدراسة النسيجية، تراوح عدد العقد اللمفية الإيجابية من 1 إلى 9 في الجهة الواحدة، في العنق إيجابي العقد تبين وجود 4 حالات (24%) تبدي انتشاراً خارج المحفظة. تطورت حالتان من النكس العقدي خارج مكان التجريف المجرى، كما أن نسبة النكس الناحي مشابهة للمرضى الذين كانت لديهم العقد سلبية في الدراسة النسيجية وهي 3%، مقارنة مع حالة المرضى إيجابيي عقد العنق دون وجود انتشار خارج المحفظة 4%. في حين ارتفعت نسبة النكس الناحي إلى 18% من الحالات التي أبدت فيها الإصابة العقدية انتشاراً خارج المحفظة. المرضى الذين لديهم أكثر من عقدتين إيجابيتين لديهم نسبة أعلى من النكس الورمي مقارنة مع المرضى الذين لديهم إصابة في عقدتين أو أقل.الخلاصة: تجريف العنق الانتخابي فعال في السيطرة على النكس الورمي في العنق، ويساهم في كشف المرضى المحتاجين لعلاج متمم بعد الجراحة.Objective: to evaluate the efficacy of the selective neck dissection in the management of the clinically node-negative neck>Study Design case histories were evaluated retrospectively.Methods the results of 75 neck dissections performed on 52 patients were studied.Results theprimarysites were oral cavity 20, oropharynx 7, hypopharynx 4, and latynx 21.14 necks (23%) were node positive on pathological examination. The number of positive nodes varied from 1 to 9 per side. Of necks with positive 4 (24%) had extracapsular spread. The median follow up was 24 months. Two recurrences developed outside the dissected field. The incidence of regional recurrences was similar in patients in whom nodes were negative on histological examination 3% when compared with patients with positive nodes without extracapsular spread 4%. In contrast regional recurrence developed in 18% of necks with extracapsular spread. This observation was statistically significant. Patients having more than two metastatic lymph nodes had a higher incidence of recurrent disease than the patients with carcinoma limited to one or two nodes.Conclusion SND is effective for controlling neck disease and serves to detect patients who require adjuvant therapy.